2009
DOI: 10.1345/aph.1m225
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Therapeutic Drug Monitoring for Ribavirin in Patients with Chronic Hepatitis C—A Critical Review

Abstract: There is conflicting evidence about the existence of a correlation between ribavirin concentrations and virologic response or development of toxicity. This inconsistent evidence, coupled with the currently employed effective strategies that maximize sustained virologic response and minimize development of anemia, precludes the utility of TDM for ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…This fact highlights the essential role of ribavirin exposure in the clearance of HCV. Pharmacokinetic and pharmacodynamic studies conducted in both HCV-monoinfected and HIV-HCVcoinfected patients have found a correlation between ribavirin plasma concentrations and achievement of both RVR and SVR [33,34]. The results of our study support that a combination of pharmacogenetic and pharmacokinetic ribavirin parameters could allow the maximum likelihood of virological response to pegIFN-ribavirin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This fact highlights the essential role of ribavirin exposure in the clearance of HCV. Pharmacokinetic and pharmacodynamic studies conducted in both HCV-monoinfected and HIV-HCVcoinfected patients have found a correlation between ribavirin plasma concentrations and achievement of both RVR and SVR [33,34]. The results of our study support that a combination of pharmacogenetic and pharmacokinetic ribavirin parameters could allow the maximum likelihood of virological response to pegIFN-ribavirin.…”
Section: Discussionsupporting
confidence: 75%
“…This is particularly true for the large number of subjects infected with HCV genotypes 1 or 4, which show particularly poor response to therapy [5]. Low baseline serum HCV-RNA levels [6,30,31] and elevated ribavirin exposure [32][33][34] have been associated with increased response rates in this subset of patients. Host genetic factors, such as SNPs nearby the IL28B gene at chromosome 19, have recently been associated with an increased likelihood of viral response in HCV-monoinfected patients [14][15][16][17], as well as in HIV-HCV-coinfected patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…23 Although a series of other individual features (eg, degree of liver fibrosis, HCV viral load at baseline, age, gender, etc) were also found to have a predictive role on treatment response, 9 the only so far identified modifiable variable that has been consistently associated to the therapeutic outcome is RBV dose and pharmacokinetic exposure. 24,25,[27][28][29][30][31] Nevertheless, in most clinical studies, RBV concentration was found to correlate with the therapeutic outcome, as also historically testified by the better treatment response seen with increased RBV doses. RBV tends to accumulate in plasma over time, and as a consequence, the pharmacokinetic parameters measured at different times since treatment initiation may show significantly different values.…”
Section: Introductionmentioning
confidence: 99%
“…Nonrandomized studies have shown that the TDM of plasma RBV levels improves the management of the therapeutic response and hematologic toxicity (15,16), despite the publication of controversial reports (17). Correlations between plasma concentrations of RBV and anemia, as well as SVR rates, have been reported, with a suggested minimum trough level above 2 g/ml at week 4 to secure SVR in patients infected with HCV genotype 1, and a maximum below 3.5 g/ml to limit the risk of anemia and treatment discontinuation (18)(19)(20).…”
mentioning
confidence: 99%